Implementation Of Problem Based Learning Model Assisted By Quiziz To Improve Learning Outcomes PGSD Student At Universitas Bhinneka PGRI - Ana, Ria Fajrin; Astutik, Leny Suryaning (Widyagogik, 2024)
The problem that occurs is that learning has not gone well. The reason is that lecturers have not created learning in accordance with the demands of technological development, not yet interesting learning. In terms of students, the lack of activities that encourage thinking activities. The objectives of this study are (1) To describe the implementation of the PBL learning model with quiz and improve student learning outcomes by using the PBL learning model assisted by quiz in Mathematics Education courses. The research method uses action research. The instruments used were observation sheets, test questions, and documentation. The subjects of this study were all 5th semester PGSD students totaling 32 students. The research data analysis technique is data reduction, data presentation, and conclusion drawing. The instruments used were observation sheets and test questions. The results of the PBL model research can improve student learning outcomes in Mathematics Education courses, the level of completeness of student learning outcomes in cycle I is known to be 76.87%, while in cycle II the level of student learning outcomes has increased by 83.59%. So the level of completeness of student learning outcomes from cycle I and cycle II increased by 6.718%, so the desired target has been achieved for the completeness of student learning outcomes, because at the end of the cycle it has reached the specified target of 70%.